Relieving residual stress in brazed joint between SiC and Nb using a 3D-SiO2-fiber ceramic interlayer. (March 2018) - Ma, Q.; Li, Z.R.; Wang, Z.Y.; Ba, J.; Niu, H.W.; Qi, J.L.; Feng, J.C.
Abstract: A robust joint between SiC and Nb was realized by using the combination of Ag-Cu-Ti + Ti composite brazing alloy and a 3D quartz-fiber braided interlayer (3D-SiO2 -fiber). The 3D-SiO2 -fiber, with ductile, loose and porous structure, can be filled up by the composite brazing alloy, which plays an important role in forming a sound joint. Furthermore, considerable and uniformly distributed α-Ti, Ti2 Cu, Cu3 Si and TiSi compounded particles in the joint effectively reduced the high coefficient of thermal expansion (CTE) mismatching between different materials. Thus the residual stress in the joint was greatly mitigated and the joint was strengthened. Graphical abstract: Highlights: The structure of 3D-SiO2 -fiber is ductile, porous and loose. The massive particles are able homogeneous distribution. The particles could reduce residual stress and strengthen the joints.